Implementation of The Principles of International Contract Law In Relation To The Agreement on Biodiversity Beyond National Jurisdiction (BBNJ) - Sirait, Hilda Angelina (Media Hukum Indonesia (MHI), 2025)
An international agreement is an international agreement that uses international law and is signed in writing. According to the 1969 Vienna Convention, an international agreement is an agreement between countries in writing and governed by international law, whether in the form of one or more documents, and whatever its name. This study will further discuss the principles of international treaty law in accordance with the 1969 Vienna Convention and additions from experts. This study uses a normative legal research method by linking the provisions of the 1969 Vienna Convention to a treaty, drawing sources from the 1969 Vienna Convention, books, articles, and websites. It is hoped that this article will help readers understand the principles of international treaty law and examples of their application in the biodiversity beyond national jurisdiction (BBNJ) treaty.